(untitled) (Security Dialogues, 2024)
The relationship between Kosovo and Serbia has been characterized by hypertension for many years. This disagreement has led to ongoing political and diplomatic disputes between two sides. In a 20th century, contained by Yugoslavia but declared independence in 2008 because of conflicts with Serbians. Serbia never consents the decision and sees the Kosovo as an integral part of Serbia. Furthermore, Kosovo accepted as heart of Orthodox Church therefore the place is very significant according to Serbian’s national identity. In the background, the conflict took place and committed a war crime because of the independence of Kosovo unacceptable to Serbia. In addition that, ethnic tensions between the majority Albanian population in Kosovo and the minority Serb population have also contributed to the ongoing tensions. In the past, tensions have increased to violent conflicts. NATO’s intervention has virtually not stopped the violence and the UN Interim Administration Mission (UNMIK) established in Kosovo. After years, the observation does not change in Serbia, but in comparison the area has stabilized. Kosovo’s independence is recognized by more than 100 countries, including the United States and most of European nations. But Serbia, Russia, China and other several countries have never recognized. Nevertheless, Kosovo’s status remains an open question in international politics. However, related topics between two country seems as to normalize in recent years but tension rises again after Russia and Ukraine war started because most people liken Kosovo and Ukraine in fact their leaders. There was the same violence on the borders of Ukraine as the Serb soldiers in Yugoslavia before. Kosovo’s concerns will be understandable once the present situation in Ukraine has been analysed. The war sparked the tension in the Balkan region that already exists. Movement of Russia concerns the worry in Kosovo because Putin frankly said that; Ukraine belongs to Russia and never think separate. Keep in view the similar attitude of Serbia and Russia, Kosovo has begun to anticipate for any move.